HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN SEPAK SILA DALAM PERMAINAN SEPAKTAKRAW PADA TIM SMK 2 PEKANBARU - Gusman, Dodi; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Sila football is a fundamental technique in the game of sepak takraw because the effort to play the ball is done by the player, both tekong and apit control the ball which aims to pass and give bait, both himself and to friends as an effort to attack the opponent. Basic football techniques. Seeing from observations and observations in the field practice, there are several problems, one of which is when passing the ball to the smasher is often not optimal and does not meet the desired expectations, even though the feeder technique and soccer technique are things that must be mastered by a player sepak takraw. The purpose of this study was to find out the relationship of eye and foot coordination with soccer skills in football takraw games on the Pekanbaru SMK 2 team. The population in this study were takraw players in state SMK 2 Pekanbaru as many as 15 people. By using the total sampling technique, the sample in this study amounted to 15 people. The instrument in this study was eye and foot coordination with sepaksila ability. The data obtained is analyzed using product moment correlation. Based on the results of research and data processing using statistical research procedures, it was concluded that for the relationship of variable X with Y variable obtained r count = 0.682> rtable = 0.532, then there is a relationship between variable X and Y, thus Ha is accepted. This means that the hypothesis is accepted at a significant level α = 0.05, in other words there is an Eye and Foot Coordination Relationship with Moral Football Ability in Sepaktakraw Games at the Pekanbaru State Vocational School 2 Team.Key Words: Eye and Foot Coordination, Football Skills